2015
DOI: 10.3390/galaxies3030113
|View full text |Cite
|
Sign up to set email alerts
|

The Flyby Anomaly in an Extended Whitehead’s Theory

Abstract: In this paper, we consider an extended version of Whitehead's theory of gravity in connection with the flyby anomaly. Whitehead's theory is a linear approximation defined in a background Minkowski spacetime, which gives the same solutions as standard general relativity for the Schwarzschild and Kerr metrics cast in Kerr-Schild coordinates. For a long time and because it gives the same results for the three classical tests-perihelion advance, light bending and gravitational redshift-it was considered a viable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 36 publications
(45 reference statements)
5
21
0
Order By: Relevance
“…These trajectories take into account the information processing of the Doppler traking of each spacecraft [29]). We have found that such acceleration can be deduced from the numerical method and that its magnitude agrees with the expected estimate provided by some modified models of gravity [1,4] as given in Eq. (25).…”
Section: Discussionsupporting
confidence: 86%
“…These trajectories take into account the information processing of the Doppler traking of each spacecraft [29]). We have found that such acceleration can be deduced from the numerical method and that its magnitude agrees with the expected estimate provided by some modified models of gravity [1,4] as given in Eq. (25).…”
Section: Discussionsupporting
confidence: 86%
“…In previous works we have proposed an extended model of Whitehead's and Whitehead‐Synge's models (Coleman, 2005; Whitehead, 2007) with the objective of quantitative a quantitive prediction for the flyby anomaly (Acedo, 2015; Bel, 2007, 2015). Although the predictions of our model agree only in order of magnitude, it must be emphasized that they come from a model without any free parameter.…”
Section: Introductionmentioning
confidence: 99%
“…where µ, R are the mass constant and radius of the planet, Ω is the angular velocity with respect to the fixed stars and r the distance of the spacecraft to the center. It was shown that this model yields a qualitative agreement with the measured anomalies in several flybys of the Earth [1]. If we apply this expression to the case of Jupiter, by taking into account that r ≃ R = 71492 km at the perijove and that the Jupiter's angular velocity is Ω = 2π/T , T = 9.9259 hours [53], we get δa = 1.0396 mm/s 2 .…”
Section: Sources Of Error and Interpretation Of The Resultsmentioning
confidence: 60%
“…Some models have suggested that the Earth's gravitational field is distorted by an unknown extra term, not taken into account in General Relativity, and that this can be interpreted as a force field with a range of a few hundred kms [5]. In the model by Acedo and Bel [1,6] an anomalous azimuthal component of the gravity acceleration is proposed. The magnitude of this extra acceleration is given by:…”
Section: Sources Of Error and Interpretation Of The Resultsmentioning
confidence: 99%